Between Morphic and Hopfian - Calugareanu Grigore; Pop Lavinia (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2013)
Relatively morphic submodules are defined and a new class of modules between morphic and Hopfian modules is singled out. Special care is given to the Abelian groups case.